Harnessing long-lived visible phosphorescence to eliminate background interference from fingermark images. Issue 17 (5th August 2021) - Parmenter, Ryan A.; Clarke, Kristen T.; Gee, William J.
Abstract : A 4-tpt fingerprint powder exhibiting long-lived phosphorescence has been developed to suppress background fluorescence. This is demonstrated using standard forensic equipment on challenging surfaces while eschewing specialized imaging techniques. Abstract : Minimising background fluorescence can enhance the visible details of treated fingerprints. Here, a 4-tpt fingerprint powder exhibiting long-lived phosphorescence is applied to this end. The powder was found to suppress background fluorescence, including on challenging surfaces, when using standard forensic equipment and eschewing specialized or bespoke imaging techniques.